The Relationship Between Anxiety and Compliance of Swab Officers in Using Masks During the Covid-19 Pandemic - Assyifa Oktavia Wiraningtyas; Yuniasih, Dewi; Rossi Desvita, Widea; Rokhmayanti, Rokhmayanti (Universitas Ahmad Dahlan, 2023)
The Covid-19 has spread in Indonesia, including Kulon Progo, causing casualties. Symptomatic patients will interact with swab officers at Wates and Nyi Ageng Serang Regional Public Hospital it can cause anxiety for the swab officers on duty. Coping with the spread of Covid-19 is by obediently wearing a mask. Anxiety is a factor that can affect a person's compliance. This study aims to determine the relationship between anxiety levels and compliance with the use of hospital swab masks. This study used an observational analytic method with a cross-sectional study approach. The sample of this study was swab officers who served at Wates and Nyi Ageng Serang Regional Public Hospital in August-September 2022 and who had met the inclusion criteria. The sampling technique of this study used total sampling with a sample of 27 people. Of the 27 samples, only 26 respondents were appropriate with inclusion criteria. Data analysis used the Chi-Square test to test the hypotheses obtained from the answers to the questionnaire as a research instrument. From the results of the analysis, it was obtained sig (2-tailed) of 0,236 (sig> 0.05), so there was no relationship between anxiety and compliance with the use of masks for swab officers at Wates and Nyi Ageng Serang Regional Public Hospital. The conclusion is the majority of respondents were female, and there was no correlation between anxiety and compliance with swab officers' use of masks at Wates Hospital and Nyi Ageng Serang Hospital. At Wates Hospital and Nyi Ageng Serang Hospital, there is no gender difference in swab workers' compliance with mask use.